"Harm or Good?": Consumer Perceptions of Corporate Strategic Giving in Schools. Issue 2 (7th September 2016) - Aitken, Robert; Watkins, Leah
Abstract : This paper reports on consumer perceptions of an in‐school strategic giving initiative as a form of Corporate Social Responsibility (CSR) to consider its social implications and to understand the complexity of children's vulnerability in this context. Results suggest that corporate benefits are not balanced by welfare gains to the children and this creates a tension between positive perceptions of the initiative and negative concerns with its targeting of children. This raises a number of ethical issues related to corporate marketing in schools and provides empirical support for earlier theoretical work in this area. The paper contributes to CSR literature by suggesting that opinions towards corporate giving are determined both by perceptions of their underlying motives and in relation to the benefits they provide to stakeholders. Finally, we provide support for the need for policy and regulatory revision with regard to children's vulnerability to in‐school marketing.